Social health assistance schemes: the case of Medical Financial Assistance for the rural poor in four counties of China - Yang Yang; Tang Xiaohui; Decoster Kristof; Meessen Bruno; Zhang Juying; Ma Xiao; Ren Xiaohui (BMC, 2011)
Abstract Background Economic transition which took place in China over the last three decades, has led to a rapid marketization of the health care sector. Today inequity in health and poverty resulting from major illness has become a serious problem in rural areas of China. Medical Financial Assistance (MFA) is a health assistance scheme that helps rural poor people cope with major illness and alleviate their financial burden from major illness, which will definitely play a significant role in the process of rebuilding Chinese new rural health system. It mainly provides assistance to cover medical expenditure for inpatient services or the treatment of major illnesses, with joint funding from the central and local government. The purpose of this paper is to review the design, funding, implementation and to explore the preliminary effects of four counties' MFA in Hubei and Sichuan province of China. Methods We used an analytical framework built around the main objective of any social assistance scheme. The framework contains six 'targeting' procedural 'steps' which may explain why a specific group does not receive the assistance it ought to receive. More specifically, we explored to what extent the targeting, a key component of social assistance programs, is successful, based on the qualitative and quantitative data collected from four representative counties in central and western China. Results In the study sites, the budget of MFA ranged from 0.8 million Yuan to 1.646 million Yuan in each county and the budget per eligible person ranged from 32.67 Yuan to 149.09 Yuan. The preliminary effects of MFA were quite modest because of the scarcity of funds dedicated to the scheme. The coverage rate of MFA ranged from 17.8% to 24.1% among the four counties. MFA in the four counties used several ways to ration a restricted budget and provided only limited assistance. Substantial problems remained in terms of eligibility and identification of the beneficiaries, utilization and management of funds. Conclusions MFA needs to be improved further although it evidences the concern of the government for the poor rural people with major illness. Some ideas on how to improve MFA are put forward for future policy making.